Exogenous Fecal Microbiota Transplantation from Local Adult Pigs to Crossbred Newborn Piglets - Hu, Luansha; Geng, Shijie; Li, Yuan; Cheng, Saisai; Fu, Xiongfeng; Yue, Xiaojing; Han, Xinyan (Frontiers in Microbiology, 2018)
This study was conducted to investigate the effect of exogenous fecal microbiota transplantation on gut bacterial community structure, gut barrier and growth performance in recipient piglets. Twelve litters of Duroc × Landrace × Yorkshire piglets of the same birth and parity were weighed and divided into two groups. One group (recipient piglets) was inoculated orally with fecal microbiota suspension of healthy adult Jinhua pigs daily from d 1 to d 11. The other (control) was given orally the same volume of sterile physiological saline at the same time. The experiment lasted 27 days. The results showed that the relative abundance of Firmicutes, Prevotellaceae, Lachnospiraceae, Ruminococcus, Prevotella, and Oscillospira in the colon of recipient piglets was increased. Proteobacteria, Fusobacteriaceae, Clostridiaceae, Pasteuriaceae, Alcaligenaceae, Bacteroidaceae, Veillonellaceae, Sutterella, Escherichia, and Bacteroides in the colon of recipient piglets were decreased. An average daily weight gain of recipient piglets was increased, and diarrhea incidence of the recipient was decreased during the trial. Intestinal morphology and tight junction barrier of recipient piglets were improved. The optical density of sIgA+ cells, the number of goblet cells and relative expressions of MUC2 in the intestinal mucosa of recipient piglets were enhanced. Protein expressions of β-defensin 2 and mRNA expressions of TLR2 and TLR4 in the intestinal mucosa of recipient piglets were also increased. These findings supported that the exogenous fecal microbiota had significant effects on animal’s growth performance, intestinal barrier function, and innate immune via modulating the composition of the gut microbiota.